Asymmetric mean reversion and volatility in African real exchange rates - Kuttu, S. (Springer New York LLC, 2018)
This study seeks to examine the asymmetric mean reversion characteristics of the real exchange rate for Egypt, Ghana, Kenya, Nigeria and South Africa. We apply a two-factor model to monthly time series data spanning the period 1972:1 to 2016:12. The empirical findings suggest that the five countries’ real exchange rate exhibit non-stationary behaviour following local currency depreciation but is strongly mean reverting following local currency appreciation. However, the mean reverting component more than offsets the non-stationary component. We also found that the time-varying conditional volatility is persistence and asymmetric in all the five countries. These findings have policy and investment implications. Knowledge of purchasing power parity may be used to forecast exchange rates, manage inflation, and implement monetary policy. Also, investors could base their investment strategies on different regimes to minimise exchange rate risk. © 2017, Springer Science+Business Media, LLC.
Keywords: Asymmetric mean reversion; GJR-GARCH; Real exchange rates; Two-factor model